Pola Pemanfaatan Generative AI Oleh Mahasiswa Dalam Penyelesaian Tugas Akademik Berdasarkan Data Deklarasi AI - Dewiyanti Fadly; Halimah Husain; Dedy Setyawan (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Generative Artificial Intelligence (Gen AI) has become increasingly integrated into higher education, creating opportunities for improving learning processes while raising concerns regarding academic integrity and responsible technology use. This study aims to identify patterns of generative AI utilization among students in completing academic assignments based on AI declaration data. A mixed-methods approach was employed involving 44 students from the Chemistry Education Program enrolled in the Kajian Kurikulum Kimia SMK course. Quantitative data were analyzed using frequency and percentage analysis, while qualitative responses were examined through content analysis. The findings indicate that most students used AI in a limited manner (86.4%), primarily for brainstorming ideas (77.3%), understanding concepts (70.5%), and developing writing frameworks (47.7%). ChatGPT was the most frequently used platform (93.2%), followed by Google Gemini (45.5%) and Canva AI (29.5%). Students generally utilized AI as a supporting tool rather than a replacement for independent work, demonstrated by their efforts to adapt AI-generated outputs to course contexts (65.9%), develop additional content (56.8%), and verify information using academic sources (93.2%). However, some students still showed potential risks related to dependency and insufficiently detailed AI interaction strategies. This study concludes that AI declaration forms can serve as valuable instruments for understanding actual AI usage patterns and promoting transparent, ethical, and responsible AI integration in higher education.